A 3D printed bio-composite removable connection system for bamboo spatial structures. (1st August 2021) - van Wassenhove, Romain; De Laet, Lars; Vassilopoulos, Anastasios P.
Abstract: A 3D printed bio-composite removable connection system for bamboo space structures is introduced in this paper. The system consists of a removable clipping connection for raw bamboo structures, adapted to the European market. The use of parametric design and 3D printing enables to have both design and production processes adapted to the non-uniform bamboo culm dimensions, while being standardisable. The resulting design possibilities are very large due to the high adaptability of the whole process. The efficiency of the introduced connection system has been validated experimentally. Standardized specimens of the bio-composite material, a connection detail (clip), and a structural component were examined experimentally to validate the design. A pyramidal structure made of bamboo culms of 30 mm of diameter and 4 mm in thickness was able to sustain a load of 7 kN in compression, proving the relevance of the proposed connection system. A finite element model was developed to model the clip behaviour and successfully compared to the experimental results.